2016
DOI: 10.1177/1087054716636936
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Therapy Involving High-Intensity Interval Training Improves the Physical Fitness, Motor Skills, Social Behavior, and Quality of Life of Boys With ADHD: A Randomized Controlled Study

Abstract: Three weeks of multimodal therapy including HIIT improved physical fitness, motor skills, certain aspects of quality of life, competence, and attention in boys with ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
1
22

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(90 citation statements)
references
References 36 publications
2
65
1
22
Order By: Relevance
“…A previous study reported that regular exercise was associated with a decrease in depression and anxiety, as well as an improvement in self esteem. 20 However, the present study did not show any statistically significant results, suggesting that the application of short-term rehabilitative horseback riding may have affected the results.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…A previous study reported that regular exercise was associated with a decrease in depression and anxiety, as well as an improvement in self esteem. 20 However, the present study did not show any statistically significant results, suggesting that the application of short-term rehabilitative horseback riding may have affected the results.…”
Section: Discussioncontrasting
confidence: 74%
“…This result supports that rehabilitative horseback riding, which had a positive effect on ADHD children's attention as a psychological exercise, improves individual performance through physical activity and social functioning, 21 and aerobic exercise improves the attention deficit disorder. 20 Unlike previous studies, just participating in the short-term rehabilitative horseback riding program showed a positive result in the improvement of the attention deficit disorder.…”
Section: Discussionmentioning
confidence: 68%
“…Overall, 8 unique studies (Bustamante, et al, 2016;Chang, Hung, Huang, Hatfield, & Hung, 2014;Choi, Han, Kang, Jung, & Renshaw, 2015;Janssen, et al, 2016;Jensen & Kenny, 2004;Kang, Choi, Kang, & Han, 2011;Lee, Lee, & Park, 2015;Meßler, Holmberg, & Sperlich, 2016) were included in the meta-analysis. One study included two physical activity arms.…”
Section: Study Selectionmentioning
confidence: 99%
“…Ein Übersichtsartikel [5] hat gezeigt, dass verschiedenste Formen des Ausdauertrainings, vor allem aber intensives Ausdauertraining sich positiv auf die Leitsymptomatik sowie die Komorbiditäten bei der kindlichen ADHS auswirken [4,6]. Kinder mit ADHS zeigen im Anschluss an (hoch) intensive körperliche Aktivität Verhaltensänderungen wie z.…”
Section: Introductionunclassified